EVALUASI SOP TELEPHONE OPERATOR DALAM MENUNJANG KELANCARAN OPERASIONAL PADA FRONT OFFICE DEPARTMENT DI KETAPANG INDAH HOTEL BANYUWANGI - Eka Afrida Ermawati; Aprilia Divi Yustita; Esa Riandy Cardias; Syifa’ Fauziyah (Journal of Innovation Research and Knowledge, 2025)
Telephone operator is part of front office which play an important role in creating first impression through telephone communication with the guests. To ensure that the operational work well, it is very important for a telephone operator to applied SOP consistenly and effectively. The aim of this study is to evaluate implementations of trainee telephone operator SOPs in supporting the operational smoothness of Front Office Department at Ketapang Indah Hotel Banyuwangi. This study employs a qualitative method with data collection techniques including observation, interview, and documentation. The results show that the telephone operators such as response accuracy and speed, professional ethics and attitude, posture and body language, communication and language, and call handling. However, in communication and language indicator, some operators were found to be inconsistent in using formal language when interacting with the guests. These findings highlight the importance of continued training to enhance operators' formal communication skills to improve operators’ communication quality in line with the hotel service standards